Impact of socio-economic and environmental factors on livestock production in Kyrgyzstan - Yang, Jiamiao; Wang, Yanwen; Zhang, Hao; Su, Yuming; Wu, Xiaoyang; Yan, Shuqi; Yang, Shuwang (Frontiers in Environmental Science, 2022)
Livestock husbandry is a key indicator of economic development, environmental protection, and food security in the world, which is vulnerable to environmental changes and economic shocks. In our study on Kyrgyzstan, we quantified the effects of socio-economic and environmental factors on the dynamics of livestock sales, self-consumption, and inventory from 2006 to 2020 using a two-period livestock production model and spatial panel model. The results showed that from 2006 to 2020, more than 50% livestock were stocked annually, which means that herders in Kyrgyzstan preferred to preserve their animals as assets to deal with unknown risks. Additionally, to gain greater profit, Kyrgyz herdsmen would expand or downsize their livestock business, tailor self-consumption, and manage inventory based on the livestock market price, loan on livestock, non-herding income, and its current stock. Our study found that the development of animal husbandry in seven oblasts of Kyrgyzstan had spatial spillover effects, which indicated that the dynamics of the animal husbandry market and environment not only affected the scale of local animal husbandry but also had an important impact on adjacent oblasts. Our research contributes to ensuring the income for herdsmen and the sustainable development of animal husbandry, thereby promoting high-quality economic development in developing countries with animal husbandry as a pillar industry.